Task Forces on Housing and Urban Development Planning of Urban Development - Planning Commission (Planning Commission, 1983)
The Task Forces on Housing and Urban Development highlighted that India’s urban population, estimated at 160 million in 1981, is poised for rapid growth, necessitating a systematic review of urban policies. Urbanisation, driven by structural economic shifts and limited agricultural absorption capacity, is both inevitable and integral to economic development. While India’s urbanisation rate remains below 25 percent, absolute increases in population are significant, with large cities and small towns experiencing varied growth rates across regions. By 2001, urban population is projected to reach 315–320 million, with substantial increases in the urban labour force, demanding over 3 million new urban jobs annually during the Seventh Plan. Effective urban planning must align with economic development, timing infrastructure and services investment to complement agricultural, industrial, and commercial growth. Existing urban policies, including Master Plans and Integrated Urban Development Programmes, have been largely piecemeal, with limited coordination between physical planning and investment. A regional and sub-regional approach is recommended, emphasizing the function and employment potential of towns rather than their size. Community participation and private investment are crucial for effective service delivery. Institutional reforms are proposed, including strengthening the Housing and Urban Development Division within the Planning Commission, integrating urban projections with economic models, and requiring “Urban Impact” statements for large-scale projects. The Ministry of Works and Housing should assume primary responsibility for detailed urban planning, ensuring that urban development is proactive, coordinated, and responsive to India’s accelerating urbanisation and employment demands.
Planning Commission, Government of India
Planning Commission, Government of India
Keywords: Urban Development, Urbanisation, Housing Policy, Urban Planning, Regional Planning, Infrastructure, Employment, Population Growth, Class I Cities, Community Participation, Investment Planning, Institutional Reform